Effectiveness of Reducing GHG Emissions With Fuel Conversion in Gas and Steam Power Plant PT PLN UPDK Belawan, North Sumatera - Suryati, Isra; Zulkarnain, Randy; Utami, Rahmi; Siregar, Naomi Febriyanti; Suyanto (DINAMIS, 2024)
Gas and Steam Power Plant (PLTGU) PT. PLN (Persero) Belawan Generation Control Implementation Unit (UPDK) is the main supplier of electricity needs in the Northern Sumatra System. In the initial period of operation, PLTGU PT. PLN UPDK Belawan uses diesel oil as fuel. The use of fuel originating from the bowels of the earth certainly produces greenhouse gas (GHG) emissions. Since 2015, this PLTGU has started using natural gas as fuel. Changes in fuel use will affect the GHG emission load resulting from the Belawan PLTGU. This research aims to analyze the GHG emission load from the two types of fuel and examine the differences in GHG emissions when the conversion of diesel fuel to natural gas occurs. The emission load calculation uses the IPCC method and guidelines from the Ministry of Energy and Mineral Resources with national emission factors, meanwhile, to carry out real difference tests using the WSR test from SPSS. The results of the emission load calculation show that there is a difference in the greenhouse gas emission load produced before using natural gas fuel and when using natural gas fuel of 20.85%. This shows that fuel conversion from diesel oil to natural gas can reduce the burden of household gas emissions